2009
DOI: 10.1155/2009/421376
|View full text |Cite
|
Sign up to set email alerts
|

Is PPARγ a Prospective Player in HIV‐1‐Associated Bone Disease?

Abstract: Currently infection with the human immunodeficiency virus-1 (HIV-1) is in most instances a chronic disease that can be controlled by effective antiretroviral therapy (ART). However, chronic use of ART has been associated with a number of toxicities; including significant reductions in bone mineral density (BMD) and disorders of the fat metabolism. The peroxisome proliferator-activated receptor gamma (PPARγ) transcription factor is vital for the development and maintenance of mature and developing adipocytes. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 91 publications
1
4
0
Order By: Relevance
“…PPARγ has been shown to be directly associated with bone turnover and bone loss, and with inhibition of aromatase activity. 33,34 Our findings strongly suggest that reduced E 2 is an independent factor for the overall bone alterations observed in MLWH. Because low BMI and body fat only influenced cortical bone parameters (area, density, and thickness) mostly at the distal tibia, a decreased weightbearing effect may also contribute to bone disease.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…PPARγ has been shown to be directly associated with bone turnover and bone loss, and with inhibition of aromatase activity. 33,34 Our findings strongly suggest that reduced E 2 is an independent factor for the overall bone alterations observed in MLWH. Because low BMI and body fat only influenced cortical bone parameters (area, density, and thickness) mostly at the distal tibia, a decreased weightbearing effect may also contribute to bone disease.…”
Section: Discussionsupporting
confidence: 50%
“…The fat distribution patterns of MLWH suggested lipodystrophy (higher trunk‐to‐total fat mass and lower leg fat mass than controls), which is related to PPARγ. PPARγ has been shown to be directly associated with bone turnover and bone loss, and with inhibition of aromatase activity 33,34 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, Rev and p55 were able to activate PPARγ in MSCs from bone marrow [ 41 ]. These observations suggested that the modulation of PPARγ by HIV proteins during HIV infection may be considered a co-factor in the lipid and bone derangement observed during the HIV infection and in some antiretroviral treatments [ 79 ]. Our data also showed that viral infection and gp120 exposure induced an up-regulation of C/EBPβ and δ mRNA expressions demonstrating that adipogenesis positive modulation is determined until the first differentiation molecular steps.…”
Section: Discussionmentioning
confidence: 99%
“…The balance between Runx2 and peroxisome proliferatoractivated receptor-γ (PPAR-γ) leads to mesenchymal differentiation into osteoblasts or adipocytes, depending on the relative activity of Runx2 and PPAR-γ, respectively [32].…”
Section: Runt-related Transcription Factor 2 (Runx2)/ppar-γ Pathway: mentioning
confidence: 99%